2015
DOI: 10.1038/mp.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study of kynurenic acid in cerebrospinal fluid: implications for psychosis and cognitive impairment in bipolar disorder

Abstract: Elevated cerebrospinal fluid (CSF) levels of the glia-derived N-methyl-d-aspartic acid receptor antagonist kynurenic acid (KYNA) have consistently been implicated in schizophrenia and bipolar disorder. Here, we conducted a genome-wide association study based on CSF KYNA in bipolar disorder and found support for an association with a common variant within 1p21.3. After replication in an independent cohort, we linked this genetic variant—associated with reduced SNX7 expression—to positive psychotic symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(122 citation statements)
references
References 49 publications
9
113
0
Order By: Relevance
“…Given the association of sucrose preference with motivational pathways that involve dopamine and the nucleus accumbens, these data suggest that although the neurotoxic pathway may have effects on some inflammation-related behaviors and contribute to neurodegeneration through glutamate signaling, the effects of inflammation on motivation (and potentially other behaviors related to frontostriatal activity including cognitive function and psychomotor performance) may be mediated by kynurenic acid and the so-called 'neuroprotective pathway' and its effects on dopamine. Consistent with this notion, data in bipolar patients have indicated that increased CSF kynurenic acid is associated with a genetic variant that is linked to cognitive dysfunction as well as IL-1β induction and subsequent activation of the KP in postmortem brain tissue (Sellgren et al, 2015). Given recent interest in the development of α7 receptor nicotinic receptor agonists for treatment of cognitive deficits and negative symptoms in schizophrenia, it is intriguing to note that early data suggested positive effects of the α7 receptor nicotinic receptor agonist TC-5619 on avolition and apathy as well as cognition in schizophrenia (Lieberman et al, 2013).…”
Section: Reviewsupporting
confidence: 53%
“…Given the association of sucrose preference with motivational pathways that involve dopamine and the nucleus accumbens, these data suggest that although the neurotoxic pathway may have effects on some inflammation-related behaviors and contribute to neurodegeneration through glutamate signaling, the effects of inflammation on motivation (and potentially other behaviors related to frontostriatal activity including cognitive function and psychomotor performance) may be mediated by kynurenic acid and the so-called 'neuroprotective pathway' and its effects on dopamine. Consistent with this notion, data in bipolar patients have indicated that increased CSF kynurenic acid is associated with a genetic variant that is linked to cognitive dysfunction as well as IL-1β induction and subsequent activation of the KP in postmortem brain tissue (Sellgren et al, 2015). Given recent interest in the development of α7 receptor nicotinic receptor agonists for treatment of cognitive deficits and negative symptoms in schizophrenia, it is intriguing to note that early data suggested positive effects of the α7 receptor nicotinic receptor agonist TC-5619 on avolition and apathy as well as cognition in schizophrenia (Lieberman et al, 2013).…”
Section: Reviewsupporting
confidence: 53%
“…Moreover, the mutant animals provided an opportunity to relate changes in these outcome measures to comparable phenomena in clinical populations with reported KP abnormalities, including patients with SZ or bipolar disorder (3, 4, 7, 8, 10, 11, 13, 15). …”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional KMO activity may, in fact, be directly related to the elevated levels of KYNA, which are also seen in the CSF and postmortem brains of patients with SZ and bipolar disorder (3, 8, 1015). Thus, as demonstrated both after pharmacological KMO inhibition (1618) and in mice with a genomic elimination of the Kmo gene (19), reduced KMO activity induces a shift in KP metabolism towards the pathway branch that produces KYNA (Supplemental Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The same study also reported an association between the KMO Arg 452 allele and the presence of psychosis during manic episodes [27]. A recent genome-wide association study linked abnormal metabolism of kynurenic acid to a specific gene associated with bipolar disorder [69]. We are intrigued by the identification of α-aminoadipate, a key regulator of kynurenic acid in the brain, as the highest-ranked metabolite in an unbiased profiling of bipolar disorder and control subjects.…”
Section: Discussionmentioning
confidence: 99%